Predicting Climate‐Driven Coastlines With a Simple and Efficient Multiscale Model. Issue 6 (26th June 2019) - Antolínez, José A. A.; Méndez, Fernando J.; Anderson, Dylan; Ruggiero, Peter; Kaminsky, George M.
Abstract : Ocean‐basin‐scale climate variability produces shifts in wave climates and water levels affecting the coastlines of the basin. Here we present a hybrid shoreline change—foredune erosion model (A COupled CrOss‐shOre, loNg‐shorE, and foreDune evolution model, COCOONED) intended to inform coastal planning and adaptation. COCOONED accounts for coupled longshore and cross‐shore processes at different timescales, including sequencing and clustering of storm events, seasonal, interannual, and decadal oscillations by incorporating the effects of integrated varying wave action and water levels for coastal hazard assessment. COCOONED is able to adapt shoreline change rates in response to interactions between longshore transport, cross‐shore transport, water level variations, and foredune erosion. COCOONED allows for the spatial and temporal extension of survey data using global data sets of waves and water levels for assessing the behavior of the shoreline at multiple time and spatial scales. As a case study, we train the model in the period 2004–2014 (11 years) with seasonal topographic beach profile surveys from the North Beach Sub‐cell (NBSC) of the Columbia River Littoral Cell (Washington, USA). We explore the shoreline response and foredune erosion along 40 km of beach at several timescales during the period 1979–2014 (35 years), revealing an accretional trend producing reorientation of the beach, cross‐shore accretional, and erosional periods through time (breathing) and alternating beach rotations that are correlated with climate indices. Key Points: A new coastal evolution model (COCOONED) combines effects from longshore and cross‐shore transport, dune erosion, and sediment supply COCOONED evolves shorelines based on climate variability in both waves and water levels COCOONED is applied in Grays Harbor County, Washington, USA, for 35 years and reveals shoreline responses at multiple scales of variability